2013
DOI: 10.1016/j.jjcc.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining achievement of early postoperative cardiac rehabilitation goal in patients with or without preoperative kidney dysfunction undergoing isolated cardiac surgery

Abstract: Preoperative CKD stage correlated significantly with the progress of early postoperative CR after cardiac surgery. Independent determinants of achieving JCS early postoperative CR guideline goal were postoperative AKI in patients with or without CKD, and POFB/PBW only in patients without CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…Poorer renal function in the post-operative period has been shown to be associated with a delayed rate of physical recovery [9,10] and early mortality following cardiac surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Poorer renal function in the post-operative period has been shown to be associated with a delayed rate of physical recovery [9,10] and early mortality following cardiac surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that early rehabilitation significantly reduced both the length of hospital stay and medical costs while providing similar clinical outcomes after cardiac surgery 3,4) . However, early rehabilitation can be delayed by various postoperative complications, such as heart failure, pulmonary complications, neurologic deficits, and acute kidney dysfunction 5,6) . Postoperative atrial fibrillation (POAF) is a common complication in patients who have undergone heart valve surgery 7) .…”
mentioning
confidence: 99%
“…Even in the normal heart, the transmitral pressure gradient is highly dependent on transvalvular flow and diastolic filling period. This gradient greatly varies with changes in heart rate, and is an important predictor of functional capacity [24,25]. In the current study, patients with a 26-mm prosthesis had a significantly higher mPG, despite a significantly smaller BSA than patients with a larger size of prosthesis.…”
Section: Discussionmentioning
confidence: 45%